2020
DOI: 10.22271/j.ento.2020.v8.i6b.8315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic factors on the population dynamics of paddy earhead bug, Leptocorisa oratorius F

Abstract: The present investigation was carried out to monitor the population dynamics and their correlation with weather parameters. The experiment result revealed that the population of bug appearance coincided with the flowering stage of the rice whereas the peak population (1.81 bugs/hill) was recorded only one week after its 1 st appearance and then after the decrease in its population gradually took place which came down to zero on the last date of observation 11 November, 2020 which clearly depicted that the gund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…However, non-significant negative correlation with minimum temperature (r=-0.037) and maximum temperature (r=-0.207). The present findings are agreement with Khare et al [26] who reported that Relative humidity was only having positive impact on the Gundhi bug population whereas the rest of the weather parameters shown negative impacts on the Gundhi bug population. These finding also supported by Sharma et al [21] found that L. acuta population showed negative non-significant correlation with minimum temperature.…”
Section: Rice Gundhi Bug (L Acuta)supporting
confidence: 93%
“…However, non-significant negative correlation with minimum temperature (r=-0.037) and maximum temperature (r=-0.207). The present findings are agreement with Khare et al [26] who reported that Relative humidity was only having positive impact on the Gundhi bug population whereas the rest of the weather parameters shown negative impacts on the Gundhi bug population. These finding also supported by Sharma et al [21] found that L. acuta population showed negative non-significant correlation with minimum temperature.…”
Section: Rice Gundhi Bug (L Acuta)supporting
confidence: 93%
“…The results of the present investigation were found to be similar with the findings of earlier researchers who observed the earhead bug population during reproductive phase of the crop [3,10]. During the reproductive phase, flowering can occur which favours the maximum population of gundhi bug coupled with high temperature and humidity [11].…”
Section: Occurrence Of L Oratorius During Ahu Season 2018 and 2019supporting
confidence: 92%
“…This shows that the HyperthyroidismQoL‐cat is sensitive to detect and quantify the effect of hyperthyroidism on the HRQoL of affected cats, and that the disease has a negative effect on the HRQoL. Interestingly, certain questions related to clinical signs of hyperthyroidism commonly described in the literature, such as diarrhea and changed affection toward the owner, 2 were among the 3 items with the lowest mean scores while questions from the domain “owner” (side effects, emotional burden) were among the 3 items with the highest mean scores. Although this might indicate that the questionnaire places a rather high value on the “owner” domain, which does not necessarily reflect the HRQoL of the cat, the owner's distress can have a substantial effect on therapy decisions, including the decision to euthanize, and should certainly be considered 32 .…”
Section: Discussionmentioning
confidence: 89%
“…Hyperthyroidism is the most common endocrine disease in middle‐aged to older cats 1 . Cats suffering from hyperthyroidism have an overproduction of thyroid hormones due to abnormal functional thyroid tissue 2 . As a result of excessive thyroid hormone levels, various clinical signs occur, including weight loss despite increased appetite, vomiting, hyperactivity, polyuria and polydipsia, diarrhea, susceptibility to respiratory distress and changes in coat quality 2 .…”
Section: Introductionmentioning
confidence: 99%